2020
DOI: 10.1159/000506832
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Treatments for Extramammary Paget Disease: A Systematic Review and Meta-Analysis

Abstract: Introduction: Surgery is commonly regarded as the mainstay of treatment of extramammary Paget disease (EMPD); however, nonsurgical approaches have gained popularity in recent years. Objectives: To review the published evidence for the efficacy and safety of nonsurgical modes of therapy for EMPD. Methods: A systematic review and meta-analysis of nonsurgical EMPD treatments was performed. The primary outcome was complete response (CR); secondary outcomes were clinical regression by ≥50%, adverse events, and recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
(101 reference statements)
0
18
0
Order By: Relevance
“…Most retrospective studies, including a large meta-analysis by Snast et al [ 16 ], indicate that EMPD seems to affect women more often, probably as a result of the condition’s predominance in the vulvar area [ 4 , 6 , 8 , 10 , 12 ]. However, in one retrospective study of 76 Japanese patients, Hatta et al have found a significantly higher prevalence in men; in this particular study, 72% were male and 28% female [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most retrospective studies, including a large meta-analysis by Snast et al [ 16 ], indicate that EMPD seems to affect women more often, probably as a result of the condition’s predominance in the vulvar area [ 4 , 6 , 8 , 10 , 12 ]. However, in one retrospective study of 76 Japanese patients, Hatta et al have found a significantly higher prevalence in men; in this particular study, 72% were male and 28% female [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical techniques have also been developed or used in vulvar EMPD, most of them as complementary treatments to the surgical ones. Snast et al, in their recent meta-analysis for non-surgical treatments for EMPD, have reviewed the efficiency of the options available in the literature, specifically radiotherapy, photodynamic therapy (PDT), laser therapy, immune response modifiers, and locally applied creams [ 16 ]. Radiation is mostly used in elderly patients where comorbidities do not allow surgical intervention, in combination with surgical treatments as adjuvant radiation [ 13 ], or in difficult anatomic areas where complete excision of the lesion is not feasible [ 16 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] In a recent review that included 12 studies (4 cohort studies and 8 cases series) with a total of 67 patients, the treatment results of RT were evaluated. 2 Although the interpretation of this analysis may be difficult because the radiation fields, doses, and schedules were not standardized between patients; the complete response rate was 97%, which is comparable with the reported rate for surgery and higher than that for other nonsurgical modalities. 2 These results show that RT can be an ideal therapeutic modality for treating extensive lesions such as that in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical interventions have also been investigated currently, with varied results. 2 Radiotherapy (RT) has been suggested as a less invasive and potentially curative treatment, with a lower risk of adverse effects, [2][3][4][5] but the existing published evidence has several limitations. Most articles report small-scale retrospective studies, referring to patients treated with large heterogeneities in terms of RT dose and technique.…”
Section: Introductionmentioning
confidence: 99%